Letter from J.W. Thomas to James Curtis Booth, December 12, 1881 - Thomas, Joseph W. (1881)
Includes a list of stock to be planted, to Booth has added in his own hand "3 flowering almond."
Keywords: Booth, James Curtis, 1810-1888; Nurseries (Horticulture); Thomas, Joseph W.